SISTEM INFORMASI GEOGRAFIS ANALISIS PENYEBARAN PUSKESMAS DI KOTA SALATIGA - Wilda Vallensia Latupeirissa; Frederik Samuel Papilaya (LPPM Unbaja, 2023)
Geographic Information System (GIS) is a system that can create, manage, analyze, and map data in computer-based information. The data to be processed by GIS is spatial data which is geographically oriented data or geographic coordinates and will produce information about the location of a place on the earth's surface. Through this system, it can produce information about the location of an area and can be accessed by users online. By utilizing GIS we can see the distribution of an object in a certain area. Public Health Center is one of the health service facilities managed by the government with the task of making efforts for public health and individual health and can be reached by the community. In this analysis, the buffering method was used where it can be seen that the distance between health centers is by the desired coverage area. The result of this buffering analysis is a circle or polygon around the object. With this analysis, it can be seen the distribution of health centers and the distance between health centers, especially in the city of Salatiga.